2021
DOI: 10.1155/2021/6264447
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Leisure Activities on the Mental Health of Older Adults: The Mediating Effect of Social Support and Perceived Stress

Abstract: As the aging continues, China has become the country with the largest older population. In order to ensure the well-being of older adults in their later years, the whole society is increasingly concerned about the mental health of older adults. In 2019, we conduct a questionnaire survey in Shaanxi Province. Stratified random sampling is used to select three representative cities, and 677 samples are selected from the survey results for research. By using the structural equation model, we aim to reveal the mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 57 publications
2
5
0
Order By: Relevance
“…These findings are consistent with the results of prior studies of the relationship between proactive coping and perceived stress ( 20 ). They also align with studies of the effect path between perceived stress and mental health ( 7 , 17 ). Although previous studies have shown that proactive coping plays an important role in improving life satisfaction, personal growth, and health ( 5 , 8 , 11 ), the underlying mediating effect of perceived stress had not previously been established.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…These findings are consistent with the results of prior studies of the relationship between proactive coping and perceived stress ( 20 ). They also align with studies of the effect path between perceived stress and mental health ( 7 , 17 ). Although previous studies have shown that proactive coping plays an important role in improving life satisfaction, personal growth, and health ( 5 , 8 , 11 ), the underlying mediating effect of perceived stress had not previously been established.…”
Section: Discussionsupporting
confidence: 84%
“…These findings echo those related to the stress-buffering model of social support ( 25 ), and deepen our understanding of the beneficial effects of social support on the occupational health of pilots during the regular prevention and control of COVID-19. Previous research has demonstrated that social support can improve mental health directly ( 17 ), and our study has shown how social support buffers the negative implications of a lack of proactive coping on mental health as a boundary condition. Thus, our study suggests that social support can also improve occupational health in the workplace by playing a compensatory role, thereby extending the literature on social support as a boundary condition.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In the context of the pandemic, the content of leisure activities of older adults has also been greatly transformed and restricted. Participation in leisure activities allows them to improve mental health [75] and to re-engage with life once freed from middleage responsibilities [76]. As argued by Rosseau [26], older adults find involvement in engaging themselves in community activities such as clubs, churches, non-governmental organizations, voluntary activities, or other social groups.…”
Section: The Socio-relational Domain Of Active Ageingmentioning
confidence: 99%
“…Social and spiritual support leads to a reduction in mental health illness risks and an increase in psychological resilience in this population. Activities such as sports and travel can increase the intrinsic motivation of older adults and thus improve their mental health [52]. Participating in social events, such as voluntary events, can improve individuals' mental health through the establishment of social connections and selfmotivations [53].…”
Section: Social Participation and Psychological Resiliencementioning
confidence: 99%